TECHNICAL EFFICIENCY OF SHALLOT FARMING IN INDONESIA : STOCHASTIC FRONTIER APPROACH - Ismiasih, Ismiasih; Jamhari, Jamhari (Jurnal Penelitian Pertanian Terapan, 2024)
This study aims to measure  the production function and  technical efficiency of shallot farms in Indonesia using a stochastic frontier and inefficiency effect model. The data used secondary data from national agricultural census data in 2013, which is consisted of  with , which is consisted of 11,206 shallot farms,  is employed as the unit of analysis. The data consists of six conventional inputs and several other background factors affecting shallot production spread across 33 provinces of Indonesia. Results from this study indicated that all inputs significanly affect shallot production in Indonesia. Labor was the most elastic input. The average value of technical efficiency of shallot farms is 0,82. The results show that shallot farms in Indonesia is still inefficient and there is a 18% chance to increase the production.   The variables of inefficiency which significaly affected the production are age of farmers, education, proportion of self finance, government subsidy, cooperative, farmers group and the degree of commercialisation. Contract farming membership is not real.